2015
DOI: 10.1099/jgv.0.000256
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hepatitis B virus (HBV) pre-genomic RNA levels and higher transcription efficiency of defective HBV genomes

Abstract: Defective hepatitis B virus (dHBV) particles contain genomes corresponding to singly spliced HBV RNA. A limited number of studies show that dHBV is present in all chronically HBVinfected patients. Clinical studies have linked dHBV and dHBV gene products to high virus loads and liver damage. The replication characteristics of dHBV genomes remain poorly understood. We found that the splice donor/acceptor sites critical for the formation of dHBV genomes are conserved across HBV genotypes. We report a novel method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Cell culture studies suggested that HBSP promotes hepatoma cell proliferation and migration [136]. Alternatively, pathogenicity of the splicing variant could be attributed to increased expression of core and HBx proteins as well as DNA replication [133, 137], as a consequence of the large deletion which prevents the transcription of 2.4-kb and 2.1-kb RNAs.…”
Section: Mutations Selected At the Immune Clearance Phase Of Chronmentioning
confidence: 99%
“…Cell culture studies suggested that HBSP promotes hepatoma cell proliferation and migration [136]. Alternatively, pathogenicity of the splicing variant could be attributed to increased expression of core and HBx proteins as well as DNA replication [133, 137], as a consequence of the large deletion which prevents the transcription of 2.4-kb and 2.1-kb RNAs.…”
Section: Mutations Selected At the Immune Clearance Phase Of Chronmentioning
confidence: 99%
“…The current study compared serum HBV RNA levels between patients with HBeAg-positive and -negative CHB 4 Hepat Mon. In Press(In Press):e62079.…”
Section: Comparison Between Patients With Hbeag-positive Andnegative mentioning
confidence: 99%
“…Theoretically, any host or viral factors that increase the production of pgRNA or block the reverse transcription of pgRNA in relaxed circular DNA may cause excess of pgRNA. Accumulating evidences suggest that excess pgRNA might present in virion-like particles and represent the majority of detectable HBV RNA in sera (3) and supernatant of HBV cell cultures (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…HBV encoded proteins may regulate each other or HBV replication 28 31 . We therefore wanted to test if the inhibition of HBsAg is independent of inhibition of other HBV encoded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Secreted and intracellular HBsAg levels were estimated using MONOLISA HBsAg Ultra ELISA kit (BioRad) as described earlier 23 , 28 . Cells transfected with HBV construct and treated with DMSO (0.5% final concentration) were used as controls.…”
Section: Methodsmentioning
confidence: 99%